Formation of ad hoc microgrids for prompt critical load pickup during blackouts by leveraging stochastic distributed energy resources. Issue 11 (10th June 2021) - Chin, Jun‐Xing; Hug, Gabriela
Abstract: Extreme weather events that are increasing in frequency and impact can cause extended disruptions to power grids. To increase the resilience of power grids, focus is shifting from infrastructure hardening to quickening the restoration of distribution systems after a disaster. One method to achieve this is through the use of microgrids leveraging distributed generation in islanded mode. While much work has been done in using microgrids for system restoration, the stochastic nature of distributed energy resources (DERs) have so far been neglected. Here, a data‐driven approach to leverage stochastic DERs to form ad hoc microgrids to supply local critical loads prior to wide‐scale system restoration is presented. The proposed method is tested on a modified IEEE European LV Test Feeder. Results show that considering the stochastic nature of the resources during microgrid formation greatly affects their supply adequacy confidence levels.